Systemic Model of Customer Relationship Management in University - Tapia Romero, Marisol; Correa Morocho, Reucher (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The research “Systemic Model of Customer Relationship Management at the National University of Cajamarca” considers theories such as: general systems theory, systemic thinking, systems approach, system dynamics and customer relationship management. The current diagnosis, approached under the Systems approach, allows the elaboration of the pictographic and causal diagrams of the aforementioned management. The Systemic Model is made up of components established in four layers, its validation determines that it adds value to the client (student) and to the National University of Cajamarca. The research methodology corresponds to a non-experimental design.